Catalytic Asymmetric Dearomatization Reactions - Zhuo, Chun-Xiang; Zhang, Wei; You, Shu-Li (Angewandte Chemie International Edition, 2012)
This Review summarizes the development of catalytic asymmetric dearomatization (CADA) reactions. The CADA reactions discussed herein include oxidative dearomatization reactions, dearomatization by Diels–Alder and related reactions, the alkylative dearomatization of electron‐rich arenes, transition‐metal‐catalyzed dearomatization reactions, cascade sequences involving asymmetric dearomatization as the key step, and nucleophilic dearomatization reactions of pyridinium derivatives. Asymmetric dearomatization reactions with chiral auxiliaries and catalytic asymmetric reactions of dearomatized substrates are also briefly introduced. This Review intends to provide a concept for catalytic asymmetric dearomatization. Breaking up the party: Arenes can be transformed efficiently into enantiomerically enriched, versatile ring systems by catalytic asymmetric dearomatization reactions. Known reaction types include oxidative dearomatization, dearomatization by Diels—Alder reactions, alkylative dearomatization of electron‐rich arenes, transition‐metal‐catalyzed dearomatization reactions (see example), and cascade reaction sequences involving asymmetric dearomatization as the key step.